Business group affiliation and financial performance in the agricultural sector of transition economies: The case of Russian agroholdings - Alisher Tleubayev; Ihtiyor Bobojonov; Taras Gagalyuk; Thomas Glauben (Journal of East European Management Studies, 2022)
The Russian agri-food sector illustrated remarkable progress over the last decade. Still, the Russian government is striving to boost production even further and has set a number of goals for the industry for the coming years. Agroholdings are believed to be the main engine not only behind the success of the industry in recent years, but they are also expected to play a key role in moving the sector towards the set targets. In spite of their increasing role, the literature on agroholdings is still in its infancy and it fails to provide a clear answer on whether they represent a more efficient form of agri-food production. To fill this gap in the literature, we utilise a manually collected panel data set of 203 corporate Russian agri-food enterprises for the years between 2012 and 2017 and provide new empirical evidence on the effects of agroholding affiliation on firms' financial performance, measured in terms of returns on assets and sales. The results of the random effects model indicate a significant positive impact of agroholding affiliation on financial performance. Further analysis reveals that this positive effect might be attributed to agroholding affiliates' better access to capital, efficient management and stimulating executive compensation systems. The paper provides empirical recommendations for policy makers and corporate executives involved in the Russian agri-food industry.
Keywords: M14; Q12; Q13; 330; agroholdings; resource dependence theory; financial performance; Russia; agriculture